Tandem inversion duplication within F8 Intron 1 associated with mild haemophilia A. (11th May 2015) - Lannoy, N.; Bandelier, C.; Grisart, B.; Reginster, M.; Ronge‐Collard, E.; Vikkula, M.; Hermans, C.
Summary In approximately 90% of mild haemophilia A (HA) patients, a missense mutation can be identified using complete gene sequencing. In this study, multiplex ligation‐dependent probe amplification analysis was performed as a second step in 10 French‐speaking Belgian with mild HA presenting no detectable causal mutation by complete sequencing of the factor VIII (FVIII) (F8) gene's 26 exons and its 1.2 kb of contiguous promoter sequence. This gene dosage technique enabled the detection of exon 1 duplications of F8 in three apparently unrelated subjects. Using array‐comparative genomic hybridization, breakpoint analysis delimited the duplication extent to 210 kb in the F8 intron 1 and VBP1 gene intragenic position. We postulated that the rearrangement responsible for this duplication, never before reported, could be attributed to a symmetrical tandem inversion duplication, resulting in a large 233 kb rearrangement of F8 intron 1. This rearranged intron should lead to the production of a small number of normal mRNA transcripts in relation to the mild HA phenotype. Our analysis of the entire F8 mRNA from index case 1, particularly the segment containing exons 1–9, revealed normal amplification and sequencing. Reduced plasma FVIII antigen levels caused by cross‐reacting material is associated with a quantitative deficiency of plasma FVIII. Male patients were unresponsive to desmopressin (1‐deamino‐8‐D‐arginine vasopressin). All patients displayed identical F8 haplotypes, despite not being related, which suggests a possible founder effect caused by a 210 kb duplication involving F8 exon 1.